Organisasi Masyarakat Sipil dalam Pembentukan Perda Zonasi Wilayah Pesisir dan Pulau Kecil di Bangka Belitung - La Ode Muhamad Muliawan; Komang Jaka Ferdian; Sarpin; Rini Archda Saputri; Bahjatul Murtasidin; Ranto (PERSPEKTIF, 2023)
This article aimed to identify the involvement of civil society organizations in the process of local policy arrangement. This descriptive-qualitative research accounted for the analysis of WALHI Bangka Belitung participation in the process of the arrangement of Regional Regulation Number 3 of 2020 concerning Zoning Plans for Coastal Areas and Small Islands of the Bangka Belitung Archipelago Province in 2020-2040. The result suggested that WALHI Bangka Belitung are actively having their contribution in organizing the zoning regulation in the forms of a series of criticisms addressed to the government and parliament through the mass media. However, it is formally recognized as unsubstantial or merely procedural participation. The involvement of elements of civil society in this case is solely in order to get around the procedure for drafting participatory legislation. On the other hand, the result emphasizes the participation of WALHI Bangka Belitung possibly is supported by the availability of political structure opportunities. First, the policy emergence seemingly representing the state’s interest to exploit the sea through tin mining instead of accommodating fishermen or coastal society interests. Second, the requirement of democratic policy arrangement is guaranteed by the Constitution by means of the availability of participation occasion.